A System for Compacting Phonebook Database - Ristov, Strahil; Lauc, Davor (2003)
A full text search phonebook database may need to be stored on a portable device with limited storage resources. We describe a system of data structures and algorithms used to produce a very compact structure with full text search capability, which enables storing 1.8 million entries Republic of Croatia phonebook in fewer than 50 MB.
Projekt MZOS
Projekt MZOS
ENG